Assessment of antimicrobial self-medication in undergraduate medical students in a rural tertiary care teaching hospital:a cross-sectional questionnaire-based study - Gurappanavar, Deepika; Manchukonda, Ravishankar; Shivamurthy, Shwetha (International Journal of Research in Medical Sciences, 2017)
Background: According to WHO’s definition, “self-medication is the selection and use of medicines by individuals to treat self-recognized illnesses or symptoms”. A sensible clinical use of antimicrobials is crucial to prevent the occurrence of antimicrobial resistance. As undergraduate medical students are aware of the various antimicrobial agents and diseases, this study assessing antimicrobial self- medication carries a significant value. Methods: A cross-sectional questionnaire-based study was conducted among the undergraduate medical students of Adichunchanagiri Institute of Medical Sciences, BG Nagar, Mandya, Karnataka. Results: The prevalence of antimicrobial self-medication among the medical undergraduates was 48.4%. Male student participation was 53.2%, whereas female students 46.8%. Among the antimicrobial agents self-medicated, azithromycin (55.6%) was the most common, followed by amoxicillin (12.3%), ciprofloxacin (7.4%), ofloxacin (6.2%), cefixime (4.9%), levofloxacin (3.7%), metronidazole (2.5%), amoxicillin + clavulanic acid (2.5%) and others (5%). The indications for self-medication reported were upper respiratory infection (66.6%), gastroenteritis (12.3%), fever (11.1%), boils (3.7%), acne, tonsillitis and urinary tract infection, 1.2% each. Reasons for seeking self-medication: About 54.4% students felt that their illness is mild in nature and 21% were confident about the illness and treatment. Choice of antimicrobial agents was based on previous prescription of physicians (51.6%) and textbook knowledge (39%). 90% of students had completed the course of treatment, 76.1% were aware of antimicrobial resistance and 92% students considered self-medication as a component of self-care. Conclusions: Our study shows that antimicrobial self-medication is widely practiced among under-graduate medical students of the institute. In this situation, faculties should create awareness and educate their students regarding advantages and disadvantages of antimicrobial self-medication.